(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This thesis examines the factors influencing Customer Relationship Management (CRM) strategies in small business operations, emphasizing their unique characteristics and challenges. Small businesses often operate with limited resources but rely heavily on building and maintaining strong customer relationships to ensure sustainability and growth. The study identifies key factors, such as organizational culture, technological adoption, employee involvement, and customer behavior, that shape the effectiveness of CRM strategies in small enterprises. By integrating theoretical frameworks, including relationship marketing and resource-based views, the research highlights how these factors interact to influence strategic decision-making. Additionally, the thesis explores the distinct characteristics of small businesses, such as their adaptability, proximity to customers, and reliance on personalized interactions, and how these traits impact CRM implementation. Through qualitative and quantitative analyses, the study aims to provide actionable insights for small business owners and contribute to the broader understanding of CRM strategies tailored to the needs of small-scale operations.